Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Orang Pribadi Jakarta Pusat pada Era Pandemi dengan Sosialisasi Perpajakan Sebagai Variabel Moderasi - Krisnawati Tarigan; Lydia Emmanuela; Deni Iskandar (Universitas Kristen Maranatha, 2022)
This study aims to examine the effect of the Implementation of the e-filing System, Tax Comprehension, and the Quality of Tax Services on Taxpayer Compliance, and to examine Taxation Socialization as a moderating variable (strengthening or weakening) the effect of independent variables on dependent variables in this study. The population in this study is an individual taxpayer in Central Jakarta. The data used is primary data with questionnaire as the instrument, and collected using a purposive sampling method where the sample was selected based on certain criteria. The results of the study indicate that the Implementation of the e-filing System significantly has positive effect on Taxpayer Compliance, Tax Comprehension significantly has positive effect on Taxpayer Compliance and the Quality of Tax Services significantly has positive effect on Taxpayer Compliance. Another result that can be concluded is that Tax Socialization is not able to be a proxy as a moderating variable in this study, Tax Socialization does not moderate the relationship between Tax Comprehension on Taxpayer Compliance, and Tax Socialization does not moderate the relationship between the Implementation of the e-filing System on Taxpayer Compliance. Keywords : Implementation of e-filing System, Tax Comprehension, Quality of Tax Services, Tax Socialization, and Tax Compliance